2020
DOI: 10.12928/telkomnika.v18i1.12447
|View full text |Cite
|
Sign up to set email alerts
|

A novel cross-coupled microstrip bandpass filter with hairpin-DGS resonators using coupling matrix technique

Abstract: This paper introduces a new design of a cross-coupled microstrip bandpass filter (MBPF) based on hairpin defected ground structure (DGS) resonators using accurate coupling matrix (CM) technique for microwave communication systems. The article presents the equivalent circuit of the suggested MBPF based on the DGS equivalent circuit model derived from the equivalent inductance and capacitance that occurs despite the presence of the slots disrupting the current in the ground layer. The paper investigates also the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In defected ground structure (DGS) design, currently it is commonly used in the application such as antennas [2]- [4], microwave filters [5]- [7], and the latest trend in microwave sensors [8], [9]. The progression of research works on the DGSs in RF and microwave for the last 10 years have shown evidences of improvement towards design realizations and performances.…”
Section: Introductionmentioning
confidence: 99%
“…In defected ground structure (DGS) design, currently it is commonly used in the application such as antennas [2]- [4], microwave filters [5]- [7], and the latest trend in microwave sensors [8], [9]. The progression of research works on the DGSs in RF and microwave for the last 10 years have shown evidences of improvement towards design realizations and performances.…”
Section: Introductionmentioning
confidence: 99%